(3QSGdI fXe GdBdi aj GdYed HGdQHY GdgdGdis - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdMeOdg (B: (3agPg QSGdI edNUg ai eYQag GdhbJ SejJgG HfXe GdBdi ai GdYed HGdQHY GdgdGdi s
(3BNQgG (B:s
(3hEf GbeJ HYO GdchcH hLgJg ebGe ejd GdTeS MUd CYeGd GdchcH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B217 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B57 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjg (B((3ejbGJ (B138) s
Keywords: (3Gdadcs